Biodegradable polylactic acid-based home textile fabric and preparation method thereof

By using modified activated carbon powder and bamboo fibers in polylactic acid-based home textile fabrics, the cross-linked network structure is formed, and the problem of slow degradation rate of existing fabrics is solved, and the high degradation rate and mechanical strength is improved, which meets environmental protection and performance. Dual demand.

CN119162703AInactive Publication Date: 2024-12-20YANTAI PACIFIC HOME FASHION CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411659173.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2024-12-20
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The degradation rate of existing biodegradable polylactic acid-based home textile fabrics is limited, making it difficult to meet environmental protection and performance needs.

Method used

The raw materials such as polylactic acid, polyhydroxybutyrate, modified activated carbon powder and bamboo fiber are used to form a cross-linking network structure through the treatment of starch and active groups, and the degradation rate and mechanical strength of the fabric are improved.

Benefits of technology

The fabric has achieved high degradation rate (180-day degradation rate >91%), high fracture strength (>127N) and water-washed fracture strength retention rate (>99%), meeting the market's dual demand for environmental protection and performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of home textile fabrics, and particularly discloses a biodegradable polylactic acid-based home textile fabric and a preparation method thereof. The home textile fabric is mainly prepared from the following raw materials in parts by weight: 70-80 parts of polylactic acid, 5-15 parts of polyhydroxybutyrate, 7-9 parts of modified activated carbon powder, 4-6 parts of bamboo fibers, 0.5-1.5 parts of an antioxidant and 0.5-1.5 parts of a lubricant; the modified activated carbon powder is obtained by treating activated carbon powder with starch, ethyl 2-chloroethoxy acetate and 2-oxo-3-ethoxycarbonyl-5-chloromethyl tetrahydrofuran. According to the home textile fabric, through mutual cooperation of the raw materials, the home textile fabric has the advantages of being high in degradability, high in degradation rate, good in breaking strength and good in breaking strength retention rate, and the requirements for good physical performance and environmental protection of the home textile fabric are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of home textile fabrics, and more specifically, to a biodegradable polylactic acid-based home textile fabric and a preparation method thereof. Background Art

[0002] Home textile fabrics are materials used to make home textiles, such as bed sheets, quilt covers, towels, pillowcases, curtains, carpets, etc., which have become an indispensable part of modern home life. In recent years, with the improvement of people's environmental awareness, biodegradable home textile fabrics have gradually become a research hotspot. This type of fabric not only has good physical properties, but also can be degraded in the natural environment, effectively reducing environmental pollution. The raw materials of biodegradable home textile fabrics in the prior art generally include polylactic acid. Polylactic acid can be decomposed into carbon dioxide and water by microbial action in the soil. It is a degradable polymer material. However, the home textile fabrics prepared using polylactic acid have a limited degradation rate and need to be further improved. Summary of the invention

[0003] In order to increase the degradation rate of home textile fabrics, the present application provides a biodegradable polylactic acid-based home textile fabric and a preparation method thereof.

[0004] In a first aspect, the present application provides a biodegradable polylactic acid-based home textile fabric, which adopts the following technical solution: A biodegradable polylactic acid-based home textile fabric, which is mainly made of the following raw materials in parts by weight: 70-80 parts of polylactic acid, 5-15 parts of polyhydroxybutyrate, 7-9 parts of modified activated carbon powder, 4-6 parts of bamboo fiber, 0.5-1.5 parts of antioxidant, and 0.5-1.5 parts of lubricant; the modified activated carbon powder is obtained by treating activated carbon powder with starch, ethyl 2-chloroethoxyacetate, and 2-oxo-3-ethoxycarbonyl-5-chloromethyltetrahydrofuran.

[0005] The biodegradable polylactic acid-based home textile fabric of the present application has a higher degradation rate, breaking strength and water-washing breaking strength retention rate through the mutual cooperation between the raw materials, and the 180-day degradation rate is greater than 91%, the breaking strength is greater than 127N, and the breaking strength retention rate after 10 washings is greater than 99%. It shows the advantages of high degradability, fast degradation rate, good breaking strength and good breaking strength retention rate, meeting market demand.

[0006] The raw materials of home textile fabrics are mainly polylactic acid and polyhydroxybutyrate, which have good biodegradability, are easy to decompose home textile fabrics, and reduce environmental pollution. Modified activated carbon powder and bamboo fiber are added to the raw materials. Bamboo fiber and modified activated carbon powder can form a cross-linked network structure, increase the breaking strength, and bamboo fiber can also promote decomposition and increase the degradation rate. At the same time, the activated carbon powder is modified, starch is loaded on the surface and pores of the activated carbon powder, and the degradation process is accelerated by starch. 2-chloroethoxyethyl acetate and 2-oxo-3-ethoxycarbonyl-5-chloromethyltetrahydrofuran are further grafted, and active groups such as ester groups, ether groups, and carbonyl groups are introduced to increase the compatibility and dispersibility of the modified activated carbon powder, and improve the interaction between the modified activated carbon powder and bamboo fiber, so that the home textile fabrics show better degradability and mechanical strength.

[0007] Optionally, the modified activated carbon powder is prepared by the following method: T1. Add activated carbon powder to water at a temperature of 50-70°C, mix, add sodium hydroxide aqueous solution to mix, then add starch aqueous solution, stir for 1-3h, filter, and obtain starch-modified activated carbon powder; T2. Add starch-modified activated carbon powder to isopropanol aqueous solution at a temperature of 50-70°C, add ethyl 2-chloroethoxyacetate and 2-oxo-3-ethoxycarbonyl-5-chloromethyltetrahydrofuran, stir for 7-9 hours, filter, wash, and dry to obtain modified activated carbon powder.

[0008] Optionally, the weight ratio of the activated carbon powder, the starch aqueous solution, ethyl 2-chloroethoxyacetate, and 2-oxo-3-ethoxycarbonyl-5-chloromethyltetrahydrofuran is 10:(80-120):(1-3):(1-3), and the mass concentration of starch in the starch aqueous solution is 1-8%.

[0009] By adopting the above technical scheme, starch is first loaded on the surface of activated carbon powder, and at the same time, sodium hydroxide is added. Under the action of sodium hydroxide, not only the starch loading amount is increased, but also the number of hydroxyl groups on the starch surface is increased. Then, 2-chloroethoxyethyl acetate and 2-oxo-3-ethoxycarbonyl-5-chloromethyltetrahydrofuran are grafted using hydroxyl groups, and active groups such as ester groups, ether groups, and carbonyl groups are introduced on the surface to increase the compatibility, dispersibility, and binding force between the modified activated carbon powder and the raw materials, thereby improving the degradation rate, breaking strength, and water-washing breaking strength retention rate of home textile fabrics, so that the modified activated carbon powder exhibits a better use effect.

[0010] In the modified activated carbon powder preparation method, sodium hydroxide aqueous solution and starch aqueous solution are prepared in advance, which not only facilitates the mixing of starch, sodium hydroxide and activated carbon powder, but also increases the dispersion uniformity and ensures the stability of the modified activated carbon powder preparation.

[0011] Optionally, the weight ratio of the activated carbon powder to the sodium hydroxide aqueous solution is 10:(2.5-7.5), and the mass concentration of sodium hydroxide in the sodium hydroxide aqueous solution is 15-25%.

[0012] By adopting the above technical scheme, the weight ratio of activated carbon powder and sodium hydroxide aqueous solution is optimized, and then the amount of sodium hydroxide added is optimized, which not only increases the loading amount of starch in starch-modified activated carbon powder, but also fully activates the starch, increases the number of hydroxyl groups on the starch surface, increases the grafting amount of ethyl 2-chloroethoxyacetate and 2-oxo-3-ethoxycarbonyl-5-chloromethyltetrahydrofuran, enhances the use effect of the modified activated carbon powder, and increases the degradability and mechanical strength of home textile fabrics.

[0013] In multiple embodiments, the mass concentration of sodium hydroxide in the sodium hydroxide aqueous solution is 20%. The mass concentration can also be set to 15%, 18%, 22%, or 25% as needed, but is not limited to the listed values. Other unlisted values ​​within the numerical range are also applicable.

[0014] Optionally, the weight ratio of the activated carbon powder, water and isopropanol aqueous solution is 1:(8-12):(8-12), and the weight ratio of water to isopropanol in the isopropanol aqueous solution is 1:(1-3).

[0015] By adopting the above technical scheme, the weight ratio of activated carbon powder, water and isopropanol aqueous solution is optimized, and then the addition amount of water and isopropanone is optimized, so that the activated carbon powder is fully dispersed in the water, and the starch-modified activated carbon powder, ethyl 2-chloroethoxyacetate and 2-oxo-3-ethoxycarbonyl-5-chloromethyltetrahydrofuran are fully dispersed in the isopropanone aqueous solution, and the raw materials are fully contacted and reacted, thereby ensuring the stability of the preparation of the modified activated carbon powder.

[0016] In multiple embodiments, the weight ratio of activated carbon powder, water, and isopropanol aqueous solution is 1:10:10. The weight ratio can also be set to 1:8:8, 1:8:10, 1:8:12, 1:10:8, 1:10:12, 1:12:8, 1:12:10, 1:12:12 as needed, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0017] In multiple embodiments, the weight ratio of water to isopropanol in the isopropanol aqueous solution is 1:2. The weight ratio can also be set to 1:1, 1:1.5, 1:2.5, 1:3 as needed, but is not limited to the listed values. Other unlisted values ​​within the numerical range are also applicable.

[0018] Optionally, the starch in the starch aqueous solution is one or more of wheat starch, corn starch, sweet potato starch, and tapioca starch.

[0019] By adopting the above technical solution, starch is optimized, which facilitates the selection of starch. Moreover, wheat starch, corn starch, sweet potato starch and cassava starch are abundant in source and cheap in price.

[0020] Optionally, the activated carbon powder in the modified activated carbon powder is one or more of coconut shell activated carbon powder, wood activated carbon powder, and coal activated carbon powder.

[0021] Optionally, the average particle size of the activated carbon powder in the modified activated carbon powder is 5-50 μm; the average length of the bamboo fiber is 5-30 mm and the average diameter is 10-100 μm.

[0022] By adopting the above technical scheme, the particle size of activated carbon powder, and the length and diameter of bamboo fiber are optimized, which not only ensures the stability of the raw material source, but also facilitates the full dispersion of modified activated carbon powder and bamboo fiber in the raw materials, thereby improving the degradation rate and breaking strength of home textile fabrics.

[0023] In multiple embodiments, the average particle size of the activated carbon powder in the modified activated carbon powder is 10 μm, and the average particle size can also be set to 5 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm as needed, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0024] In multiple embodiments, the average length of the bamboo fiber is 10 mm and the average diameter is 30 μm. The average length can also be set to 5 μm, 15 μm, 20 μm, 25 μm, or 30 μm as needed. The average diameter can also be set to 10 μm, 20 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, or 100 μm as needed, but is not limited to the listed values, and other unlisted values ​​within the numerical range are equally applicable.

[0025] Optionally, the starch aqueous solution is prepared by the following method: adding starch to water and mixing, heating to 90-95° C., continuing stirring for 5-20 minutes, and cooling to room temperature to obtain the starch aqueous solution.

[0026] Optionally, the antioxidant is one or more of antioxidant 1010, antioxidant 330, antioxidant 264, antioxidant B225, and antioxidant B215; The lubricant is one or more of stearamide, N,N'-ethylene bis stearamide, ethyl silicone oil, and butyl stearate.

[0027] By adopting the above technical solution, antioxidants and lubricants are optimized, which facilitates the selection of antioxidants and lubricants. Moreover, antioxidants can effectively improve the antioxidant properties of home textile fabrics and extend their service life, while lubricants can improve the processing properties of raw materials, reduce friction resistance, and improve the quality of home textile fabrics.

[0028] Optionally, the antioxidants are two kinds of antioxidants, antioxidant 1010 and antioxidant B225, and the weight ratio of antioxidant 1010 to antioxidant B225 is 1:(1-3). In multiple embodiments, the weight ratio of antioxidant 1010 to antioxidant B225 is 1:2, and the weight ratio can also be set to 1:1, 1:1.5, 1:2.5, 1:3 as needed, but it is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0029] In a second aspect, the present application provides a method for preparing the biodegradable polylactic acid-based home textile fabric, which adopts the following technical solution: A method for preparing the biodegradable polylactic acid-based home textile fabric mainly comprises the following steps: S1, mixing polylactic acid, polyhydroxybutyrate, modified activated carbon powder, bamboo fiber, antioxidant, and lubricant to obtain a mixture; S2, heating and melting the mixture, extruding and granulating, and obtaining a polylactic acid-based masterbatch; S3, melt-spinning the polylactic acid-based masterbatch, spinning yarn, and weaving the yarn to obtain home textile fabrics.

[0030] By adopting the technical solution, the preparation of home textile fabrics is facilitated.

[0031] Optionally, in step S2, the heating and melting temperature is 220-230°C; In step S3, the melt spinning temperature is 210-220°C and the spinning rate is 1500-2000 m / min.

[0032] By adopting the above technical scheme, the heating melting temperature, melt spinning temperature and spinning rate are limited to ensure that the mixture is fully mixed during the heating melting process, enhance the uniformity of the mixture, and also ensure that the polylactic acid-based masterbatch has good fluidity during the melt spinning process, enhance the spinning efficiency and ensure the quality of home textile fabrics.

[0033] In multiple embodiments, in step S2, the heating and melting temperature is 225°C. The temperature can also be set to 220°C, 222°C, 228°C, or 230°C as needed, but is not limited to the listed values. Other unlisted values ​​within the numerical range are also applicable.

[0034] In multiple embodiments, the melt spinning temperature is 215°C and the spinning rate is 1800 m / min. The temperature can also be set to 210°C, 212°C, 218°C, or 220°C as needed. The spinning rate can also be set to 1500 m / min, 1600 m / min, 1700 m / min, 1900 m / min, or 2000 m / min as needed. However, the present invention is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0035] In summary, this application has at least the following beneficial effects: 1. The biodegradable polylactic acid-based home textile fabric of the present application has the advantages of high degradability, fast degradation rate, good breaking strength and good breaking strength retention rate through the mutual cooperation between raw materials. The 180-day degradation rate is greater than 91%, the breaking strength is greater than 127N, and the breaking strength retention rate after 10 washings is greater than 99%, so that the home textile fabric has good physical properties and meets environmental protection requirements.

[0036] 2. The modified activated carbon powder of the present application first loads starch on the surface and pores of the activated carbon powder, using starch to accelerate degradation, improve degradability and degradation rate. Then, 1-chlorododecane and ethyl 4-(2-chloroethane acylamino)benzoate are grafted, and active groups such as ester groups, ether groups, and carbonyl groups are introduced to increase compatibility and dispersibility, as well as the interaction between the activated carbon powder and bamboo fiber, thereby improving the degradation rate, breaking strength, and breaking strength retention rate of home textile fabrics, so that the home textile fabrics show better comprehensive performance. DETAILED DESCRIPTION

[0037] In order to make the present application easier to understand, the present application will be further described in detail below in conjunction with the examples, which are merely illustrative and are not intended to limit the scope of application of the present application. The raw materials or components used in the present application can be obtained through commercial routes or conventional methods unless otherwise specified.

[0038] Preparation Example Preparation Example 1 A modified activated carbon powder is prepared by the following method: T1. At a temperature of 60°C, add 10g of activated carbon powder to 100g of water and stir for 5min. Add 5g of sodium hydroxide aqueous solution and stir for 10min. Then add 100g of starch aqueous solution and stir for 2h. Then filter to obtain starch-modified activated carbon powder.

[0039] Among them, the activated carbon powder is coconut shell activated carbon powder, the average particle size of the activated carbon powder is 10 μm, and it is selected from Zhengzhou Yongkun Environmental Protection Technology Co., Ltd.; the mass concentration of sodium hydroxide in the sodium hydroxide aqueous solution is 20%; the mass concentration of starch in the starch aqueous solution is 5%, the starch is corn starch, and it is selected from Hebei Chaoyan New Material Technology Co., Ltd.

[0040] The starch aqueous solution was prepared by the following method: adding starch to water, stirring for 1 min, heating to 95° C., continuing stirring for 10 min, cooling to 23° C., and obtaining the starch aqueous solution.

[0041] T2. Add starch-modified activated carbon powder to 100 g of isopropanol aqueous solution at 60°C and stir for 5 min. Add 2 g of ethyl 2-chloroethoxyacetate and 2 g of 2-oxo-3-ethoxycarbonyl-5-chloromethyltetrahydrofuran and stir for 8 h. Then filter and wash three times with water, using 50 g of water each time, and dry to constant weight to obtain modified activated carbon powder.

[0042] Wherein, the weight ratio of water to isopropanol in the isopropanol aqueous solution is 1:2.

[0043] Preparation Example 2 A modified activated carbon powder is prepared by the following method: T1. Add 10 g of activated carbon powder to 100 g of water at 60°C and stir for 5 min. Add 2.5 g of sodium hydroxide aqueous solution and stir for 10 min. Then add 80 g of starch aqueous solution and stir for 3 h. Then filter to obtain starch-modified activated carbon powder.

[0044] Among them, the activated carbon powder is coconut shell activated carbon powder, the average particle size of the activated carbon powder is 10 μm, and it is selected from Zhengzhou Yongkun Environmental Protection Technology Co., Ltd.; the mass concentration of sodium hydroxide in the sodium hydroxide aqueous solution is 20%; the mass concentration of starch in the starch aqueous solution is 5%, the starch is corn starch, and it is selected from Hebei Chaoyan New Material Technology Co., Ltd.

[0045] The starch aqueous solution was prepared by the following method: adding starch to water, stirring for 1 min, heating to 95° C., continuing stirring for 10 min, cooling to 23° C., and obtaining the starch aqueous solution.

[0046] T2. Add starch-modified activated carbon powder to 100 g of isopropanol aqueous solution at 60°C and stir for 5 min. Add 1 g of ethyl 2-chloroethoxyacetate and 3 g of 2-oxo-3-ethoxycarbonyl-5-chloromethyltetrahydrofuran and stir for 7 h. Then filter and wash three times with water, using 50 g of water each time, and dry to constant weight to obtain modified activated carbon powder.

[0047] Wherein, the weight ratio of water to isopropanol in the isopropanol aqueous solution is 1:2.

[0048] Preparation Example 3 A modified activated carbon powder is prepared by the following method: T1. At a temperature of 60°C, add 10g of activated carbon powder to 100g of water and stir for 5min. Add 7.5g of sodium hydroxide aqueous solution and stir for 10min. Then add 120g of starch aqueous solution and stir for 1h. Then filter to obtain starch-modified activated carbon powder.

[0049] Among them, the activated carbon powder is coconut shell activated carbon powder, the average particle size of the activated carbon powder is 10 μm, and it is selected from Zhengzhou Yongkun Environmental Protection Technology Co., Ltd.; the mass concentration of sodium hydroxide in the sodium hydroxide aqueous solution is 20%; the mass concentration of starch in the starch aqueous solution is 5%, the starch is corn starch, and it is selected from Hebei Chaoyan New Material Technology Co., Ltd.

[0050] The starch aqueous solution was prepared by the following method: adding starch to water, stirring for 1 min, heating to 95° C., continuing stirring for 10 min, cooling to 23° C., and obtaining the starch aqueous solution.

[0051] T2. Add starch-modified activated carbon powder to 100 g of isopropanol aqueous solution at 60°C and stir for 5 min. Add 3 g of ethyl 2-chloroethoxyacetate and 1 g of 2-oxo-3-ethoxycarbonyl-5-chloromethyltetrahydrofuran and stir for 9 h. Then filter and wash three times with water, using 50 g of water each time, and dry to constant weight to obtain modified activated carbon powder.

[0052] Wherein, the weight ratio of water to isopropanol in the isopropanol aqueous solution is 1:2.

[0053] Example

[0054] Table 1 Amount of each raw material used in non-woven fabrics (unit: kg)

[0055] Example 1 A biodegradable polylactic acid-based home textile fabric, the raw materials and raw material ratios of which are shown in Table 1.

[0056] Among them, polylactic acid is polylactic acid 4032D; polyhydroxybutyrate is polyhydroxybutyrate 1001MD; the average length of bamboo fiber is 10 mm, the average diameter is 30 μm, and it is selected from Shandong Jiumian Textile Co., Ltd.; the antioxidants are antioxidant 1010 and antioxidant B225, and the weight ratio of antioxidant 1010 to antioxidant B225 is 1:2; the lubricant is N,N'-ethylene bisstearamide; the modified activated carbon powder is prepared by the method of Preparation Example 1.

[0057] A method for preparing a biodegradable polylactic acid-based home textile fabric mainly comprises the following steps: S1. Add polyhydroxybutyrate, modified activated carbon powder, bamboo fiber, antioxidant and lubricant to polylactic acid, stir for 5 minutes, and obtain a mixture.

[0058] S2, heating and melting the mixture, extruding and granulating, and obtaining polylactic acid-based masterbatch.

[0059] The heating and melting temperature is 225°C.

[0060] S3, melt-spinning the polylactic acid-based masterbatch, spinning yarn, and weaving the yarn to obtain home textile fabrics.

[0061] The melt spinning temperature was 215° C. and the spinning rate was 1800 m / min.

[0062] Example 2 A biodegradable polylactic acid-based home textile fabric, which is different from Example 1 in that the raw material ratio of the home textile fabric is different, and the raw material ratio is shown in Table 1.

[0063] Example 3 A biodegradable polylactic acid-based home textile fabric, which is different from Example 1 in that the raw material ratio of the home textile fabric is different, and the raw material ratio is shown in Table 1.

[0064] Example 4 A biodegradable polylactic acid-based home textile fabric, which is different from Example 1 in that the source of the modified activated carbon powder in the raw materials of the home textile fabric is different, and the modified activated carbon powder is prepared by the method of Preparation Example 2.

[0065] Example 5 A biodegradable polylactic acid-based home textile fabric, which is different from Example 1 in that the source of the modified activated carbon powder in the raw materials of the home textile fabric is different, and the modified activated carbon powder is prepared by the method of Preparation Example 3.

[0066] Comparative Example Comparative Example 1 A biodegradable polylactic acid-based home textile fabric, which is different from Example 1 in that an equal amount of polylactic acid is used to replace modified activated carbon powder and bamboo fiber in the raw materials of the home textile fabric.

[0067] Comparative Example 2 A biodegradable polylactic acid-based home textile fabric, which is different from Example 1 in that an equal amount of modified activated carbon powder is used to replace bamboo fiber in the raw materials of the home textile fabric.

[0068] Comparative Example 3 A biodegradable polylactic acid-based home textile fabric, which is different from Example 1 in that an equal amount of bamboo fiber is used to replace modified activated carbon powder in the raw materials of the home textile fabric.

[0069] Comparative Example 4 A biodegradable polylactic acid-based home textile fabric, which is different from Example 1 in that an equal amount of activated carbon powder is used to replace modified activated carbon powder in the raw materials of the home textile fabric.

[0070] Comparative Example 5 A biodegradable polylactic acid-based home textile fabric, which differs from Example 1 in that, in the raw materials of the home textile fabric, in the preparation method of the modified activated carbon powder, an equal amount of 3-aminopropyltrimethoxysilane is used to replace starch, ethyl 2-chloroethoxyacetate, and 2-oxo-3-ethoxycarbonyl-5-chloromethyltetrahydrofuran in the starch aqueous solution.

[0071] Comparative Example 6 A biodegradable polylactic acid-based home textile fabric, which differs from Example 1 in that, in the raw materials of the home textile fabric, in the preparation method of the modified activated carbon powder, ethyl 2-chloroethoxyacetate and 2-oxo-3-ethoxycarbonyl-5-chloromethyltetrahydrofuran are replaced with an equal amount of water.

[0072] Comparative Example 7 A biodegradable polylactic acid-based home textile fabric, which differs from Example 1 in that in the raw materials of the home textile fabric, in the preparation method of the modified activated carbon powder, an equal amount of 2-chloroethoxyethyl acetate is used to replace 2-oxo-3-ethoxycarbonyl-5-chloromethyltetrahydrofuran.

[0073] Comparative Example 8 A biodegradable polylactic acid-based home textile fabric, which differs from Example 1 in that, in the raw materials of the home textile fabric, in the preparation method of the modified activated carbon powder, an equal amount of 2-oxo-3-ethoxycarbonyl-5-chloromethyltetrahydrofuran is used to replace ethyl 2-chloroethoxyacetate.

[0074] Performance Testing The home textile fabrics obtained in Examples 1-5 and Comparative Examples 1-8 were respectively taken, and the following performance tests were performed on the home textile fabrics. The test results are shown in Table 2.

[0075] Among them, according to GBT 19277.1-2011 "Determination of the ultimate aerobic biodegradability of materials under controlled composting conditions using the method of measuring the released carbon dioxide Part 1: General method", the home textile fabrics were landfilled for 180 days and the 180-day degradation rate was calculated.

[0076] According to GB / T3923.1-2013 “Tensile properties of textile fabrics Part 1: Determination of breaking strength and elongation at break (Strip method)”, the breaking strength and breaking strength after 10 washes of home textile fabrics were tested, and the breaking strength retention rate after 10 washes was calculated.

[0077] Table 2 Test results

[0078] As can be seen from Table 2, the home textile fabric obtained in this application has a high degradation rate, with a 180-day degradation rate of 91.2-92.8%, showing better degradability and accelerating the degradation rate. It also has a high breaking strength and water-washing breaking strength retention rate, with a breaking strength of 127.3-129.6N, a breaking strength of 126.3-129.1N after 10 washings, and a breaking strength retention rate of 99.2-99.6% after 10 washings, showing better breaking strength and water-washing breaking strength retention rate, meeting market demand.

[0079] Example 1 is compared with Comparative Examples 1-3. In Comparative Example 1, no modified activated carbon powder and bamboo fiber are added to the raw materials of home textile fabrics; in Comparative Example 2, modified activated carbon powder is added to the raw materials of home textile fabrics; in Comparative Example 3, bamboo fiber is added to the raw materials of home textile fabrics; in Example 1, modified activated carbon powder and bamboo fiber are added to the raw materials of home textile fabrics. It can be seen that by adding modified activated carbon powder and bamboo fiber to the raw materials at the same time and utilizing the synergistic effect between them, the degradation rate, breaking strength and water-washing breaking strength retention rate are significantly improved, so that the home textile fabrics show better comprehensive performance.

[0080] Comparative Examples 4-6 are compared. In Comparative Example 4, activated carbon powder is added to the raw materials of home textile fabrics; in Comparative Example 5, modified activated carbon powder is added to the raw materials of home textile fabrics, and the modified activated carbon powder is obtained by treating the activated carbon powder with 3-aminopropyltrimethoxysilane; in Comparative Example 6, modified activated carbon powder is added to the raw materials of home textile fabrics, and the modified activated carbon powder is obtained by treating the activated carbon powder with starch. It can be seen that treating the activated carbon powder with 3-aminopropyltrimethoxysilane has little effect on the degradation rate, but can improve the breaking strength. Treating the activated carbon powder with starch can significantly improve the degradation rate.

[0081] Compare Example 1 and Comparative Examples 7-8. The modified activated carbon powder of Comparative Example 7 is obtained by treating activated carbon powder with starch and ethyl 2-chloroethoxyacetate; the modified activated carbon powder of Comparative Example 8 is obtained by treating activated carbon powder with starch and 2-oxo-3-ethoxycarbonyl-5-chloromethyltetrahydrofuran; the modified activated carbon powder is added to the raw materials of home textile fabrics in Example 1, and the modified activated carbon powder is obtained by treating activated carbon powder with starch, ethyl 2-chloroethoxyacetate and 2-oxo-3-ethoxycarbonyl-5-chloromethyltetrahydrofuran. It can be seen that on the basis of modifying the activated carbon powder with starch, further grafting ethyl 2-chloroethoxyacetate and 2-oxo-3-ethoxycarbonyl-5-chloromethyltetrahydrofuran, and introducing active groups such as ester groups, ether groups, and carbonyl groups, the bonding force between the modified activated carbon powder and the raw materials can be significantly increased, and the breaking strength and the water-washing breaking strength retention rate can be improved.

[0082] It should be noted that the embodiments described above are only used to explain the present application and do not constitute any limitation to the present application. The present application is described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present application may be modified as specified within the scope of the claims of the present application, and the present invention may be revised without departing from the scope and spirit of the present application. Although the present application described therein relates to specific methods, materials and embodiments, it does not mean that the present application is limited to the specific examples disclosed therein. On the contrary, the present application can be extended to all other methods and applications with the same functions.

Claims

1. A biodegradable polylactic acid-based home textile fabric, characterized in that: The home textile fabric is mainly made of the following raw materials in parts by weight: 70-80 parts of polylactic acid, 5-15 parts of polyhydroxybutyrate, 7-9 parts of modified activated carbon powder, 4-6 parts of bamboo fiber, 0.5-1.5 parts of antioxidant and 0.5-1.5 parts of lubricant; the modified activated carbon powder is obtained by treating activated carbon powder with starch, ethyl 2-chloroethoxyacetate and 2-oxo-3-ethoxycarbonyl-5-chloromethyltetrahydrofuran.

2. The biodegradable polylactic acid-based home textile fabric according to claim 1, characterized in that: The modified activated carbon powder is prepared by the following method: T1. Add activated carbon powder to water at a temperature of 50-70°C, mix, add sodium hydroxide aqueous solution to mix, then add starch aqueous solution, stir for 1-3h, filter, and obtain starch-modified activated carbon powder; T2. Add starch-modified activated carbon powder to isopropanol aqueous solution at a temperature of 50-70°C, add ethyl 2-chloroethoxyacetate and 2-oxo-3-ethoxycarbonyl-5-chloromethyltetrahydrofuran, stir for 7-9 hours, filter, wash, and dry to obtain modified activated carbon powder.

3. The biodegradable polylactic acid-based home textile fabric according to claim 2, characterized in that: The weight ratio of the activated carbon powder, the starch aqueous solution, ethyl 2-chloroethoxyacetate, and 2-oxo-3-ethoxycarbonyl-5-chloromethyltetrahydrofuran is 10:(80-120):(1-3):(1-3), and the mass concentration of starch in the starch aqueous solution is 1-8%.

4. The biodegradable polylactic acid-based home textile fabric according to claim 2, characterized in that: The weight ratio of the activated carbon powder to the sodium hydroxide aqueous solution is 10:(2.5-7.5), and the mass concentration of sodium hydroxide in the sodium hydroxide aqueous solution is 15-25%.

5. The biodegradable polylactic acid-based home textile fabric according to claim 2, characterized in that: The weight ratio of the activated carbon powder, water and isopropanol aqueous solution is 1:(8-12):(8-12), and the weight ratio of water to isopropanol in the isopropanol aqueous solution is 1:(1-3).

6. The biodegradable polylactic acid-based home textile fabric according to claim 2, characterized in that: The starch in the starch aqueous solution is one or more of wheat starch, corn starch, sweet potato starch and cassava starch.

7. The biodegradable polylactic acid-based home textile fabric according to claim 1, characterized in that: The average particle size of the activated carbon powder in the modified activated carbon powder is 5-50 μm; the average length of the bamboo fiber is 5-30 mm and the average diameter is 10-100 μm.

8. The biodegradable polylactic acid-based home textile fabric according to claim 1, characterized in that: The antioxidant is one or more of antioxidant 1010, antioxidant 330, antioxidant 264, antioxidant B225, and antioxidant B215; The lubricant is one or more of stearamide, N,N'-ethylene bis stearamide, ethyl silicone oil, and butyl stearate.

9. A method for preparing a biodegradable polylactic acid-based home textile fabric according to any one of claims 1 to 8, characterized in that: The main steps are as follows: S1, mixing polylactic acid, polyhydroxybutyrate, modified activated carbon powder, bamboo fiber, antioxidant, and lubricant to obtain a mixture; S2, heating and melting the mixture, extruding and granulating, and obtaining a polylactic acid-based masterbatch; S3, melt-spinning the polylactic acid-based masterbatch, spinning yarn, and weaving the yarn to obtain home textile fabrics.

10. The method for preparing a biodegradable polylactic acid-based home textile fabric according to claim 9, characterized in that: In step S2, the heating and melting temperature is 220-230°C; In step S3, the melt spinning temperature is 210-220°C and the spinning rate is 1500-2000 m / min.

Citation Information

Patent Citations

  • Fully biodegradable polylactic acid composite material and preparation method thereof

    CN104804387A

  • Degradable antibiosis polylactic acid elastic fiber and preparation method thereof

    CN106917157A

  • Bamboo fiber polylactic acid composite material and preparation method

    CN107383815A

  • Environment-friendly degradable fiber shoe material and preparation method thereof

    CN109735074A

  • PBAT / PLA starch-based completely biodegradable material and preparation method thereof

    CN111410822A